2007
DOI: 10.1039/b617059e
|View full text |Cite
|
Sign up to set email alerts
|

Microbial source tracking: a forensic technique for microbial source identification?

Abstract: As the requirements of the Water Framework Directive (WFD) and the US Clean Water Act (USCWA) for the maintenance of microbiological water quality in 'protected areas' highlight, there is a growing recognition that integrated management of point and diffuse sources of microbial pollution is essential. New information on catchment microbial dynamics and, in particular, the sources of faecal indicator bacteria found in bathing and shellfish harvesting waters is a pre-requisite for the design of any 'programme of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…However, the use of chemical or microbial tracers is limited to following only a limited number of inputs at any one time whilst faecal pollution source tracking techniques are relatively new, no standard methods have yet been proposed, sample analysis is often complicated and requires costly analytical equipment and many techniques require reference libraries. The application of these latter methods on a catchmentwide basis is still uncertain and more comparison studies are required in order to determine which methods are best suited to catchment scale studies (Meays et al, 2004;Stapleton et al, 2007).…”
Section: Article In Pressmentioning
confidence: 99%
“…However, the use of chemical or microbial tracers is limited to following only a limited number of inputs at any one time whilst faecal pollution source tracking techniques are relatively new, no standard methods have yet been proposed, sample analysis is often complicated and requires costly analytical equipment and many techniques require reference libraries. The application of these latter methods on a catchmentwide basis is still uncertain and more comparison studies are required in order to determine which methods are best suited to catchment scale studies (Meays et al, 2004;Stapleton et al, 2007).…”
Section: Article In Pressmentioning
confidence: 99%
“…In a recent watershed study, MST data using qualitative (presence/absence) markers of bovine-specific (CF128) and human-specific (HF183) Bacteroidales genotypes were more reliable on high-flow samples with higher concentrations of culturable fecal indicators and could not discriminate precisely between livestock-and human-derived feces in the larger land use pattern (17). The reason for this outcome may have been the use of nonquantitative MST data and/or the presence of free DNA or extracellular DNA, which can persist in marine water, freshwater, and sediment for up to 55 days, 21 days, or 40 days, respectively (6).…”
mentioning
confidence: 99%
“…Current routine monitoring protocols discourage sampling during the same tidal state, instead suggesting a minimum of seven days between sampling events, a procedure that is supported by our study (Anon, 2014). Sporadic and unpredictable rainfall events however, probably influence the concentrations of bacteria in shellfish harvesting waters more than tidal state alone, by increasing the levels of agricultural run-off and potential for partially treated sewage entering the sea (Henroth et al, 2002;Stapleton et al, 2007;Laws et al, 2008;Kay et al, 2005). …”
Section: Discussionmentioning
confidence: 98%
“…Subsequently, the classification grade assigned to an individual shellfish bed impacts not only consumers, but also the shellfish industry, as it dictates the level of post-harvest treatment required for shellfish products at each classification grading, and could promote either a change in management practice or a temporary closure of the harvesting area. Previous research has shown that environmental factors such as seasonality, tidal state and rainfall events may alter concentrations of E. coli detected within shellfish tissues and hence affect the classification assigned to a harvesting area (Stapleton et al, 2007;Riou et al, 2007;Kay et al, 2008a). Subsequently, the classification assigned to each shellfish harvesting area has substantial socio-economic implications (e.g.…”
Section: Introductionmentioning
confidence: 98%